TEACHING SPEAKING USING CARTOON FILM TO THE FIRST YEAR STUDENTS OF MTsN GONDANGREJO KARANGANYAR IN 2005/2006 ACADEMIC YEAR - RIFAI , MUHAMMAD (2006)
This study is aimed at describing the implementation, effectiveness and students response on teaching speaking using cartoon film. The result of this research is expected to contribute the teaching learning of English in junior high school The study was implemented in MTsN Gondangrejo Karanganyar using action research. The writer took 10 students of the first year students as the subject of the research. The object of the research was students' answers on the written test of each practice in teaching speaking using cartoon film implementation. The writer compared the result of the pre-test and three practices -in teaching speaking using cartoon film implementations- to collect the required data and then made a percentage of speaking correctness. The result of research show that :(1) the average result of the first cycle was 74% of correctness on students' speaking (2) the average result of the second cycle was 79% of correctness on students' speaking(3) the average result of the third cycle was 88% of correctness on students' speaking. The average result of the students' speaking correctness is 80% of correctness. The average result of the students' speaking correctness in pre-test was 28%. Considering of the result of the research there is improvement on the percentage of speaking correctness from the first, second and third cycle. It can be concluded that teaching speaking using cartoon film is an effective technique to improve the students' competence.